MATHEMATICAL MODELLING OF MASS EXCHANGE PROCESSES BETWEEN FLOW AND ALLUVIAL SEDIMENTS - M. R. Magomedova (Вестник Дагестанского государственного технического университета: Технические науки, 2017)
Objectives. The aim is to improve the mathematical model of the motion of channelfill deposits in terms of clarifying one of the main relationships on which the sediment flow rate depends: the frequency of pulsations of the vertical fluid velocity component with hydraulic flow parameters.Methods. The mathematical model is developed using probability theory and the theory of runs of random processes, taking into account the normal distribution of the horizontal and vertical components of the instantaneous flow velocities and the Rayleigh law of the distribution of their maxima.Results. As a result of the modelling, information was obtained concerning the volumes and areas of the zones of influence of increased turbidity on the aquatic bioresources of the Gizeldon River. The operation of the Gizeldon hydroelectric power station have led to the loss of zoobenthos habitats, the destruction of bottom biocenoses, the loss of food organisms of plankton and benthos, a decrease in the fodder base of fish and the direct death of the ichthyofauna. An assessment of the damage caused to aquatic bioresources from the operation of the Gizeldon hydroelectric power station was carried out. As a result, it was proved that the negative influence of the "turbidity loop" in the lower tail of the river, taking into account the critical values of suspended matter concentration in water will be traced for 3.7 km. The amount of damage to aquatic bioresources in physical terms is about 1.5 tons due to the destruction of the fodder base of fish and the deterioration of habitat conditions in the zone of increased turbidity.Conclusion. The results of mathematical modelling were tested on field data materials and used to calculate the turbidity of the Gizeldon River flow during the reconstruction of the Gizeldon hydroelectric power station. The results of the approbation of the mathematical model of the motion of channel-fill sediment are presented in order to identify the areas of increased turbidity during the assessment of the damage to the water resources of the Gizeldon River.